Dampak Kecerdasan Buatan (Artificial Intelligence) Terhadap Pemustaka Dalam Mencari Informasi di UPT Perpustakaan Universitas Islam Negeri Raden Fatah - Prasetio, Ardi; Winanda, Tri (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
A library is an organizational unit aimed at collecting, storing, managing, and organizing a structured collection of library materials to be utilized by users as a source of information and as an enjoyable learning facility. Users who frequently use artificial intelligence will become dependent on it, but artificial intelligence can also assist them in easily finding the information they seek. This research employs a literature review method by searching for materials in terms of literature through journals, books, and magazines by exploring the internet and utilizing the existing artificial intelligence in the library of UIN Raden Fatah Palembang. This study is conducted to ascertain the impact of artificial intelligence on both the library and users wherever they seek information. Thus, the aim of this research is to investigate the extent of the impact of artificial intelligence on library users at UIN Raden Fatah Palembang. The use of artificial intelligence greatly aids library users in seeking information, and time efficiency in finding what they desire is a primary factor in using artificial intelligence in the library. The relevance of information provided by artificial intelligence becomes a distinct preference for library users in searching for information, and the advancement of technology in current developments is an attraction for libraries in facilitating librarians in seeking information in the library.